Corporate Turnaround in SME - case studies from CEE - Kurnas, Martin; Jaklová, Martina L.; Raiman, Alexander; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2011)
The presented master thesis is intended to serve as a guide to the corporate turnarounds for small and medium enterprises. In the first part, the theoretical background related to corporate turnaround is outlined complemented with specific aspects of the CEE region and the Czech Republic. In the next part, a comprehensive turnaround framework based on theoretical research is developed. The final part presents a case study of a small Czech company that went through a turnaround and evaluates the company's turnaround actions from the perspective of suggested theoretical framework.
Vedoucí práce: Martina L. Jaklová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2012
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2012
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses